Cost Efficiency of the Egyptian Banking Sector: A Panel Data Analysis - Ismail Hassan; Ammar Jreisat (International Journal of Economics and Financial Issues, 2016)
Based on a two stage method this paper investigates the determinants of the cost efficiency (CE) of Egyptian banking sector. Employing data envelopment analysis (DEA). We compare the CE of large, medium and small banks and the CE of foreign and domestic banks using a balanced panel which cover 14 banks operating in Egypt from 1997 to 2013. In the first stage, CE scores are computed using an input-oriented DEA. At the second stage, CE scores are regressed on a set of potential explanatory variables in a logit model. While the CE scores show large improvements in the early and third phases of financial deregulation. Over the entire sample period, CE has declined at the rate of 0.963% per annum. Our finding indicates that age, loan to net interest margin, return on equity and good management practices positively affects banks CE and number of bank branches negatively affects bank CE.